Optimizing bone-metal implant interfaces: the role of bio-ceramic coatings in improving stability and tissue metabolism - Balasubramani, Geetha; J., Premkumar; J., Paul Pradeep (Frontiers in Materials, 2025)
IntroductionBone replacement is often necessary for patients experiencing pain or swelling in the knee or limb bone region due to osteoarthritis and other bone- related diseases. During surgery, a new bone implant made of metal-on-metal (titanium, cobalt-chromium) or polymer-on-metal (polyethylene on titanium) is used. A significant drawback of these implants is the accumulation of metal or polymer debris, leading to inflammation and infections. Infections or inflammation caused by bacterial adherence to the implant surface result in biofilm formation at the implantation site. Additionally, infections can arise from metal debris generated by the friction and movement of the knee joint, known as implant-associated infections.MethodsThis research aims to develop a bio-ceramic- based composite coating for metal implants. The composite comprises beta- tricalcium phosphate, pectin, gelatine, and polyvinylpyrrolidone (PVP) applied to a 12 mm cortical titanium screw. This coating is designed to enhance the biocompatibility, antibacterial properties, and anti-inflammatory activities of the bone screw, promoting cell growth around the implant and creating a viable environment at the implantation site.Results and DiscussionPrimary characterization of the composite coating materials was conducted using Scanning Electron Microscopy (SEM) with Energy Dispersive X-ray (EDX) analysis and Fourier Infrared Spectroscopy (FTIR). In-vitro antibacterial testing, anti-inflammatory testing, and degradation.